AETIOLOGIC AGENTS AND ANTIMICROBIAL SUSCEPTIBILITY PATTERN ASSOCIATED WITH URETHRAL CATHERTERISED PATIENTS AT THE FEDERAL MEDICAL CENTRE, UMUAHIA ABIA STATE, NIGERA - Odinaka, Iwu, Justus; Vincent, Otokunefor, Tosanwunmi; Blaise, Chikere, Chioma. (IJRDO - JOURNAL OF BIOLOGICAL SCIENCE, 2015)
The increasing rate of catheter associated urinary tract infection (CAUTI) and the resistance in empirical antibiotic therapy became a threat to mankind. This study therefore identify microbial pathogens associated with bacteriuria and UTI in patients with indwelling urethral catheters and determine their susceptibility patterns to commonly used antimicrobial agents. A total of 1000 urine specimens from 1000 patients were used in the study and analyzed for white blood cell count and bacteria count. The specimens were cultured on Blood, MacConkey and CLED agar plates. Pure colonies of the isolated organisms were biochemically characterized and antibiogram was performed on each of the bacterial isolate. The commonest indication for catheterization is bladder outlet obstruction (BOO, 30%) followed by Congestive cardiac failure (CCF, 15%). Seven hundred and eighty patients were urine culture positive for microbial pathogens with 684 bacterial isolates, 96 (9.6 %) yeast while 220 (22%) were bacteriologically sterile. Patients above 80years had the highest total bacterial count of 13.1 x 104 Cfu/ml followed by patients between the age of 61 – 80 and 41 – 60 with total heterotrophic bacterial count of 12.1 x 104 Cfu/ml and 13.1 x 104 Cfu/ml, respectively. Staphylococcus spp. were the commonest pathogens with 584 isolates (85.4%), followed by Pseudomonas spp. 48 (7.0%), Klebsiella spp. 30 (4.4%), Escherichia spp. 15 (2.2%) and Proteus spp. 7 (1.0%). The invitro antibiotic susceptibility pattern of the organisms presents a mixed response (susceptible / resistance) to commonly used antibiotic s such as Ceftazidine, Cefurosime. Gentamycin, Cefuroxime, Nitrofurotoin, Ciprofloxacin, Cofrimoxazola, Cloxacilline, Erythromycin, Streptomycin, Tetracycline, Chloramphenicol, Augmentin, Ofloxacin. There is high level of resistance to antibiotics by the organisms isolated and no single antibiotic used in the study was able to eliminate all the isolates identified. There is 100% resistance by all the organisms to Cotrimoxazole. Analysis of Variance (ANOVA) showed insignificant difference between means for the various parameters examined at P ≤ 0.05.